2018
DOI: 10.1002/bjs.10887
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the oncological safety of autologous fat transfer after breast cancer

Abstract: Lipofilling ok

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 78 publications
(189 reference statements)
4
32
0
Order By: Relevance
“…At least 41 non-overlapping studies have previously reported LRR and DM rates after AFT, but the oncologic safety of lipofilling still remains debated, despite the fact that the great majority of evidence suggests similar outcomes between AFT and control patients [7]. We observed that LRR and DM rates were similar between AFT and control patients after exact matching according to baseline cancer-related features.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…At least 41 non-overlapping studies have previously reported LRR and DM rates after AFT, but the oncologic safety of lipofilling still remains debated, despite the fact that the great majority of evidence suggests similar outcomes between AFT and control patients [7]. We observed that LRR and DM rates were similar between AFT and control patients after exact matching according to baseline cancer-related features.…”
Section: Discussionmentioning
confidence: 53%
“…After adjusting for confounders in a regression model accounting for adjuvant treatments and BMS, AFT was still not associated with increased LRR (HR 0.87, p=0.69) or DM (HR 0.82, p=0.55). Recently, a large meta-analysis on 4,292 patients demonstrated a non-significant incidence rate difference in LRR of -0.15% per year between AFT and control patients, providing robust evidence of AFT safety after breast cancer [7]. However, the mean follow-up from AFT procedure was only 2.7 years for included studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several metaanalyses and systematic reviews have unanimously concluded that autologous fat transfer does not lead to an increased rate of locoregional breast cancer recurrence. [65][66][67][68][69][70] However, as mentioned previously, a higher rate of biopsies exists with patients who have undergone fat grafting to the breasts compared with the general population, as fat necrosis may be difficult to distinguish radiographically from breast cancer. 21,22 That is, to date there is a substantial amount of evidence that fat grafting remains a safe and highly effective option for cosmetic breast surgery in patients with a history of breast cancer.…”
Section: Oncological Safetymentioning
confidence: 99%